1996
DOI: 10.1056/nejm199603213341203
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia as a Risk Factor for Deep-Vein Thrombosis

Abstract: M a r t i n d e n H e u e r , M.D., T e d K o s t e r , M.D., H e n k J. B lo m , Ph.D., G e r a r d M.J. Bos, M.D., E r n e s t B r i ë t , M.D., P i e t e r H. R e its m a , P h .D ., J a n P. V a n d e n b r o ljo k e , M.D., and F rits R. R o sen d a a l, M .D .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
471
5
14

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 980 publications
(501 citation statements)
references
References 21 publications
11
471
5
14
Order By: Relevance
“…Although in our study the mean decrease in plasma tHcy in the tamoxifen group was approximately 0.5 ,umol 1-', it was as high as 2-3 ,umol 1-' in subjects with baseline concentrations higher than 9 ,umol 1-'. Hyperhomocysteinaemia is a risk factor not only for atherothrombotic diseases but also for venous thrombosis (Falc6n et al, 1994;den Heijer et al, 1996). Thus, the sporadic risk of venous thromboembolism observed in breast cancer patients treated with tamoxifen (Fisher et al, 1989;McDonald et al, 1995) could be ascribed to the drug inhibitory effect on plasma antithrombin III (Mannucci et al, 1996) or to its partial agonistic effects on other oestrogen-regulated target systems, possibly outweighing the protective effect due to the decrease in tHcy levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although in our study the mean decrease in plasma tHcy in the tamoxifen group was approximately 0.5 ,umol 1-', it was as high as 2-3 ,umol 1-' in subjects with baseline concentrations higher than 9 ,umol 1-'. Hyperhomocysteinaemia is a risk factor not only for atherothrombotic diseases but also for venous thrombosis (Falc6n et al, 1994;den Heijer et al, 1996). Thus, the sporadic risk of venous thromboembolism observed in breast cancer patients treated with tamoxifen (Fisher et al, 1989;McDonald et al, 1995) could be ascribed to the drug inhibitory effect on plasma antithrombin III (Mannucci et al, 1996) or to its partial agonistic effects on other oestrogen-regulated target systems, possibly outweighing the protective effect due to the decrease in tHcy levels.…”
Section: Discussionmentioning
confidence: 99%
“…4 Hyperhomocysteinaemia has also been linked with deep venous thrombosis, 7 vascular disease in SLE 8 and tentatively with a number of other conditions including dementia 9,10 and pre-eclampsia. 11,12 There are however problems with the current data.…”
Section: Thcy and Cardiovascular Diseasementioning
confidence: 99%
“…Multiple risk factors for developing a postoperative DVT have been identified and include advanced age, prolonged immobilization, obesity, and prior history (both personal and familial) of DVT or PE [19]. Moreover, a number of studies have shown hereditary prothrombotic genes and/or hematologic abnormalities lead to hypercoagulable states [3,8,12,18,19,22]. The majority of these previous studies have retrospectively observed an increased frequency of one or two abnormalities, such as activated protein C deficiency or hyperhomocysteinemia, in nonorthopaedic patients who have developed a DVT or PE.…”
Section: Introductionmentioning
confidence: 99%